Social Media and its Potential Impacts on Multicultural Education in Turkey - Koc-Damgaci, Fadime; Aydin, Hasan (MODESTUM LTD, 2018)
The purpose of this study is to learn the perceptions of social media users regarding multicultural education in Turkey. With this goal in mind, a short film was created that summarized the issue of multicultural education, which was shared via social media. After viewing the film, the views of the participants who had expressed comments concerning multicultural education were taken for evaluation, and 95.65% of participants harbored positive perceptions about multicultural education. Furthermore, the collected data were analyzed employing a thematic analytical method. The themes found were: alienation, social justice and equality, empathy and tolerance and cultural diversity and difference. On examining the results, it emerged that participants thought that, because multicultural education, discrimination, injustice and alienation would disappear and increased empathy, tolerance and justice would emerge.
Keywords: multiculturalism; multicultural education; diversity; tolerance; social media; Turkey; ATTITUDES; Education & Educational Research